Analysis Of Cash Flow And Liquidity In Measuring Financial Performance At Pt. Adhi Karya (Persero) Tbk On The Indonesia Stock Exchange - Fauzi R. Rahim, Melani Abd. Rakhman Laba (STIE AMKOP, 2023)
The purpose of this study is to determine and analysis PT. Adhi Karya (Persero) Tbk's financial performance using cash flow ratios and liquidity ratios over the previous 5 (five) years. PT. Adhi Karya (Persero) Tbk's financial reports for the 5 (five) quarters between 2015 and 2019 make up the population in this analysis. This study uses PT. Adhi Karya (Persero) Tbk's 5 (five) period 2015-2019 balance sheets, income statements, and cash flow statements as its data samples. Documentation is used as the technique of data gathering for this investigation. The cash flow ratio used in the analysis shows poor financial performance. This is due to the fact that the company cannot meet its upcoming obligations as determined by the cash flow ratio calculations, which show that the operating cash flow ratio (OCFR), the cash coverage ratio of current liabilities (CCRCL), and the total debt ratio (TDR) are all below one (1). However, from 2015 to 2019, the liquidity ratio, namely the Current Ratio (CR), shows that PT. Adhi Karya (Persero) Tbk has achieved a great deal financially. This is so because the value of the Current Ratio is higher than the norm for the business sector. From 2016 to 2019, the Cash Ratio has been below the industry average, indicating poor performance. Keywords: Cash Flow, Financial Performance, and Liquidity.